The contribution of Sensory Processing Sensitivity and internalized attachment representations on emotion regulation competencies in school-age children - Sperati, Alessandra; Acevedo, Bianca P.; Dellagiulia, Antonio; Fasolo, Mirco; Spinelli, Maria; D’Urso, Giulio; Lionetti, Francesca (Frontiers in Psychology, 2024)
Introduction: As captured by the individual trait of Sensory Processing Sensitivity (SPS), highly sensitive children perceive, process and responds more strongly to stimuli. This increased sensitivity may make more demanding the process of regulating and managing emotions. Yet, developmental psychology literature also showed that other variables, as those related to the rearing environment, are likely to contribute to the process of regulating emotions. With the current contribution, we aim to bridge two lines of research, that of attachment studies and that of SPS, by investigating the additive and interactive contribution of SPS and internal working models of attachment representations on emotion regulation competencies in school-aged children. Method: Participants were N = 118 Italian children (mean age: 6.5, SD = .58 years, and 51.8% female) with their mothers. Children’s positive attachment representations were rated observationally through the Manchester Child Attachment Story Task procedure during an individual session at school. Mothers reported on children SPS trait and emotion regulation competencies completing the Highly Sensitive Child Scale-parent report and the Emotion Regulation Checklist. We performed and compared a series of main and interaction effect models. Results: SPS was not directly associated with emotion regulation but it was significantly associated with positive attachment representations in predicting emotion regulation. Highly sensitive children showed poorer emotion regulation when the internalized representations were low in maternal warmth and responsiveness. When driven by sensitive and empathic attachment representation, highly sensitive children showed better emotion regulation than less-sensitive peers, suggesting a for better and for worse effect. Discussion: Highly sensitive children are not only more vulnerable to adversities but also show better emotion regulation competencies when supported by positive internal working models of attachment relationships. Overall, findings shed light on the link between SPS and attachment and suggest that working for promoting secure attachment relationships in parent-child dyads may promote better emotion regulation competences, particularly in highly sensitive children.